New Development of US Air Warfare Concept and Capability - Guo Zhengyu (Hangkong bingqi, 2023)
The United States continues to develop operational concepts and capabilities, and develops weapons from the perspective of combat systems, and undertakes key technology research, leads the innovative direction of the US military capabilities construction with the development of the field of air control operations. From the four aspects of combat concept, combat platform, situational awareness and air combat weapons, this paper analyzes the construction focus and development direction of the US air control operations concept and capability, and summarizes its development characteristics. It provides a reference for capabilities construction and technical development.